Health empowerment scripts: Simplifying social/green prescriptions - Lawson, Justin T.; Wissing, Ross; Henderson-Wilson, Claire; Snell, Tristan; Chambers, Timothy P.; McNeil, Dominic G.; Nuttman, Sonia (Frontiers in Psychology, 2022)
Social prescriptions are one term commonly used to describe non-pharmaceutical approaches to healthcare and are gaining popularity in the community, with evidence highlighting psychological benefits of reduced anxiety, depression and improved mood and physiological benefits of reduced risk of cardiovascular disease and reduced hypertension. The relationship between human health benefits and planetary health benefits is also noted. There are, however, numerous barriers, such as duration and frequencies to participate in activities, access, suitability, volition, and a range of unpredictable variables (such as inclement weather, shifting interests, and relocating home among others) impeding a comprehensive approach to their use on a wider scale. From a multidisciplinary perspective, this commentary incorporates a salutogenic and nature-based approach to health, we also provide a range of recommendations that can be undertaken at the patient level to assist in shifting the acknowledged systemic barriers currently occurring. These include using simple language to explain the purpose of health empowerment scripts, ensuing personal commitment to a minimum timeframe, enabling ease of access, co-designing a script program, providing ongoing motivational support, and incorporating mindfulness to counter unexpected disruptions.